Individuum as a function of desire. Maurizio Lazzarato and Bernard Stiegler on philosophy by Gilles Deleuze. - Kłos-Czerwińska, Paulina (Hybris, 2019)
The objective of this article is to present the philosophy of Gilles Deleuze, seen from the point of view of two contemporary authors, namely: Maurizio Lazzarato and Bernard Stiegler. The main assumption here is that its main revolutionary potential boils down to the value that is attributed to the notion of “desire”. The very power of this notion consists in counteracting the processes of reduction of human experience to the level of symbolic and affective misery. The degrading power of media and capitalist societies’ technologies as described by Lazzarato and Stiegler may give an insight into the dangers of being a disaffected individual.